Disputes in the Civil Realm as a Justification for Eliminating Criminal Acts from The Perspective of The New Criminal Code: Study of Decision Number 225/Pid.B/2019/PN. Btl - Diaudin; Cahya Wulandari; Ali Masyhar Musyid (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
This research investigates significant changes in the criminal law approach to disputes in the civil realm, specifically focusing on the justification for excluding certain criminal acts under the new Criminal Code. This shift reflects the evolution of criminal law towards a more equitable and human rights-oriented system of law enforcement. The main objective of this research is to analyze the implications and changes introduced by the new Criminal Code concerning the recognition of civil disputes as a justification for eliminating criminal acts. Additionally, the research aims to understand the impact of these changes on criminal law practice and their effect on justice within the legal system. This study employs normative legal research methods, involving the analysis of laws, legal regulations, court decisions, and relevant legal literature. A qualitative approach is used to examine and understand the changes in the new Criminal Code and their practical implications for criminal law enforcement. The findings indicate that the new Criminal Code provides greater recognition of civil disputes as a valid justification for eliminating criminal liability. This change reflects efforts to create a criminal law system that is more inclusive and sensitive to ethical values, morality, and justice. In practice, this shift alters the approach to law enforcement in cases involving civil disputes, aligning the criminal law system more closely with principles of fairness and human rights.